2015
DOI: 10.1039/c5nr05250e
|View full text |Cite
|
Sign up to set email alerts
|

Zeeman effect on surface electron transport in topological insulator Bi2Se3nanoribbons

Abstract: Topological insulators have exotic surface states that are massless Dirac fermions, manifesting special magnetotransport properties, such as the Aharonov-Bohm effect, Shubnikov-de Haas oscillations, and weak antilocalization effects. In the surface Dirac cone, the band structures are typically closely related to the p-orbitals and possess helical orbital texture. Here we report on the tunability of the transport properties via the interaction between the magnetic field and the spin-orbital angular momentum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…Theoretically, the inplane magnetic field will only shift the position of the surface Dirac point in momentum space [54,55] and cause a net in-plane spin polarization [56]. A deformation of the Fermi pocket corresponding to the spin-density redistribution is also suggested [57]. In all, the spin momentum locking and the prohibition of backscattering in topological surface states is not destroyed in an in-plane magnetic field.…”
Section: Appendix F: Angle Dependence Of Dhva Oscillation Amplitude Imentioning
confidence: 99%
“…Theoretically, the inplane magnetic field will only shift the position of the surface Dirac point in momentum space [54,55] and cause a net in-plane spin polarization [56]. A deformation of the Fermi pocket corresponding to the spin-density redistribution is also suggested [57]. In all, the spin momentum locking and the prohibition of backscattering in topological surface states is not destroyed in an in-plane magnetic field.…”
Section: Appendix F: Angle Dependence Of Dhva Oscillation Amplitude Imentioning
confidence: 99%
“…Combining these results with the phenomena observed in our samples, it is clear that the parallel-field MR in Bi 2 Se 3 could be negative or positive, or even tuned from positive to negative with the increase of the magnetic field strength. Wang et al 43 suggested that Bi Se antisite defects induced local magnetic moments that were realigned when a magnetic field was applied, reducing the spin-dependent scattering and resulting in a decrease in the total resistance of the Bi 2 Se 3 sample. However, this simple argument concerning defects could not account for various behaviors of the parallel-field MR in this study.…”
Section: Background Magnetoresistancesmentioning
confidence: 99%
“…Transport measurements have revealed that the collective spin polarization of TI surface states is aligned by the current. 43 When the magnetic field is perpendicular to the current, it is parallel to the spin polarization direction; conversely, when the field is parallel to the current, it is perpendicular to the spin polarization of the surface current. In an ideal 3D TI thin film in which each of top and bottom surfaces can be treated as a 2D system, the principal effect of a parallel field is to simply shift surface states in momentum space.…”
Section: Background Magnetoresistancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a crossover from diffusive transport behaviors in the WAL regime to variable range hopping transport in the Anderson localization regime is demonstrated in ultrathin (Bi 1− x Sb x ) 2 Te 3 film, in which negative MR emerges when the electron system becomes strongly localized . The negative MR in individual Bi 2 Se 3 nanoribbons under the in‐plane magnetic field can be explained based on the Zeeman energy induced deformation of the surface Dirac cone and the spin‐dependent scattering on local magnetic moments . The similar properties are also observed in thick films, for example, in doped Bi 2 Te 3 film with thickness of 300 nm, an inflection from WAL surface state to WL bulk state and the negative MR cusp due to bulk state take place in the parallel MR curve .…”
Section: Introductionmentioning
confidence: 98%